2016
DOI: 10.1186/s12889-016-3158-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of tobacco and alcohol use with ageing self-perceptions in older people in Ireland

Abstract: Background: Health behaviour patterns in older groups, including tobacco and alcohol use, are key factors in chronic disease prevention. We explore ageing self-perceptions as motivating factors behind smoking and drinking alcohol in older adults, and the complex reasons why individuals engage harmfully in these behaviours. Methods: Cigarette and alcohol use was assessed in a large cross-sectional national sample aged 50 years and above from the Irish Longitudinal Study on Ageing (TILDA) (n = 6,576). The Brief … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
2
12
1
2
Order By: Relevance
“…Outcomes in this category included unhealthy diet, medication noncompliance, excessive drinking, and smoking. Results from a sample of 6,576 Irish older persons found negative self-perceptions of aging predicted increased risk of harmful drinking and smoking [68].…”
Section: Impact Of Ageism On Health Of Older Persons: Individual Levelmentioning
confidence: 99%
“…Outcomes in this category included unhealthy diet, medication noncompliance, excessive drinking, and smoking. Results from a sample of 6,576 Irish older persons found negative self-perceptions of aging predicted increased risk of harmful drinking and smoking [68].…”
Section: Impact Of Ageism On Health Of Older Persons: Individual Levelmentioning
confidence: 99%
“…Older adults (aged 66–80) in this study identified the lowest mean of items “not good about drinking” and the lowest score on the importance of changing drinking habits. These findings may be because, consistent with the literature, older adults may not fully understand the risks of drinking, define moderate use above recommended limits, or do not think cutting down on drinking levels is important (Masters, 2003; Morgan et al, 2009; Villiers-Tuthill, Copley, McGee, & Morgan, 2016). In addition, while most internet interventions for alcohol misuse have been designed for younger populations (e.g., college students) (Arnaud et al, 2016; Bewick et al, 2008; Tait & Christensen, 2010), our findings showed some differences in responses to specific items to both “what is not good about drinking” and “barriers to changing drinking habits” between younger and older adults.…”
Section: Discussionmentioning
confidence: 71%
“…Acceptance of love and remarriage in older age was associated with more smoking, majority smoking a pack a day or less, in men but less smoking in women. A study observed that older adults who reported stronger perceptions of control over negative consequences of aging (those with positive ageism) have increased smoking and drinking as potential coping behaviors (Villiers-Tuthill et al, 2016). Similarly, in our study, men who reported acceptance, positive ageism, were more likely to be smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Acceptance of love and remarriage in older age was associated with more drinking, majority drinking less than once a month. Not only is drinking used as a coping behavior to counteract the negative consequences of aging, but it is also often used as a facilitator for social engagement (Kelly et al, 2018; Villiers-Tuthill et al, 2016). Therefore, the association between acceptance and drinking could be due to the higher level of social activity in individuals who report acceptance.…”
Section: Discussionmentioning
confidence: 99%